Metastatic Hepatic Epithelioid Hemangioendothelioma In 10 Years Old Boy; A Rare Case Report - Alia Ahmad; Aysha Akram; Isra Iqbal; Imran Hashim; Shehla Arshad; Masood Shah; Fariha Sahrish (Gandhara University, 2023)
OBJECTIVES Epithelioid Hemangioendothelioma is an infrequent vascular neoplasm of intermediate malignant potential oddly affecting children. It is primarily noted in soft tissues, the stomach, breast, spleen, brain, and liver. No definite risk factor is identified in children. However, following WWTR1-CAMTA1 and YAP1-TFE3 gene fusions are frequently seen in these tumours. We present a case of very rare childhood Epithelioid Hemangioendothelioma of the liver in a ten-year-old boy. A 10-year-old boy presented with abdominal pain, mild weight loss, and abnormal liver function tests. Radiologically, hepatic, pulmonary, and bony lesions are noted. The biopsy report showed Epithelioid Hemangioendothelioma confirmed by an Immunohistochemical panel. Due to the lack of facilities in our centre, palliative treatment was given to the patient. Surgical resection, liver transplant, and radiofrequency ablation were impossible due to widespread hepatic and pulmonary disease. The patient was resistant to any medical treatment. The patient died at the seventh-month follow-up. HEHE is a scarcely seen tumour with no definite management protocol. Surgical resection is the preferred treatment for resectable tumours. In non-resectable extensive bifocal tumours, like in our case, the preferred treatment is radio-frequency ablation and hepatic transplant. The overall survival is trivial due to the non-compliant nature of the disease.